Humanization of the Mechanism of Children Collective Influence to the Personality in the Aspect of Vasyl Sukhomlynskyi’s Pedagogics - Buchkivs’ka, Galyna (Pedagogical Discourse, 2013)
On the basis of the analysis of historic-pedagogical sources, pedagogical views onto the mechanism of collective influence to the personality have been revealed, which V.O. Sukhomlynskyi studied as a serious problem of educational work. To this belong the exchange of information in the process of communication; realization of personality spiritual life of collective body as a consequence of his or her own efforts, as a part of intellectual life of a personality; feeling of personality care of the collective body about him or her, perception of good as a responsibility to become better; state (position) of the personality in the system of interrelations; positive example of the collective body; stimulating of self-concept of the personality; exacerbation of personality’s need in self-education.